Laboratory learning’s role on chemistry self-concept: a mixed methods approach - Base, Derek John (My University, 2024)
This study examines the impact of hands-on chemistry laboratories in shaping secondary students’ chemistry self-concepts. Utilizing a mixed methods approach, the research sought to address how students’ chemistry self-concept varied during the first semester of an introductory chemistry course and give voice to students’ understanding of the role that laboratories play in their chemistry self-concept development. Data collection involved qualitative and quantitative methods, including surveys, open-ended responses, and semi-structured student interviews. Findings revealed that students formed a stable chemistry self-concept quickly during their introductory course, with some groups experiencing no variation during the first semester. Additionally, the findings highlight that students enrolled in a laboratory-intensive chemistry course highly valued the influence of hands-on laboratory experiments in shaping their chemistry self-concept, particularly those with lower chemistry self-concepts. Conclusions underscore the importance for educators and curriculum developers to recognize the role of chemical experiments in shaping students’ chemistry self-concept development. Recommendations for future research encourage the investigation of teachers' understanding of students’ development of their chemistry self-concept, a call to investigate students outside of honors chemistry, and further investigation into students' perception of inquiry and non-inquiry laboratories.
Keywords: Chemistry self-concept; Chemistry learning